The interaction of sulphur dioxide in aqueous suspension of magnesite and DTA studies - Temel, Hamdi; Ziyadanoğullari, Berrin; Boybay, Mustafa (My University, 2004)
Sulphur dioxide was treated with magnesite in aqueous suspension. Sulphur dioxide taken from a gas cylinder was passed through the mixture of reactive magnesite, water and iodine solution. The absorbed and unabsorbed amount of sulphur dioxide on solid and liquid phases and the concentration of Ca 2+ and Mg 2+ ions were determined by means of iodometric titrations and Atomic Absorption Spectrophotometer, respectively. The effects of contact time, the activated temperatures of absorbent and equilibrium pH on the chemical absorption of SO 2 were examined. For magnesite the maximum amount of absorbed SO 2 in the liquid phase was found to be 15.2 g (activated at 500°C) for 10 g absorbent/250 ml water, and in the solid phase, it was found to be 6.5 g (activated at 800°C). The Differential Thermal Analyses (DTA) technique has been used to follow the reaction products and modifications in the solid phase. As a result it has been found that the sulphur dioxide reacts with the carbonate as well as oxide and hydroxide produced from its calcination and hydration. © 2004 Taylor & Francis Ltd.
Die wechselwirkung von schwefeldioxid in wässriger suspension von magnesit und dta-studien
Keywords: Absorption; DTA studies; Magnesite; Sulphur dioxide